Eksplorasi Obesitas Sebagai Faktor Komorbid Covid-19: A Systematic Review: Exploration of Obesity as a Comorbid Factor of Covid-19: A Systematic Review - Mukhlidah Hanun Siregar; Mustika Arumbinang; Junengsih Junengsih (Fakultas Farmasi, Universitas Mulawarman, Samarinda, Indonesia, 2022)
Obesity is one of the comorbidities of COVID-19 which has been widely reported to have an effect on the care patients needed. This study was carried out using a Systematic Review approach to explore the effects and mechanisms that occur due to obesity in COVID-19 patients. A total of 23 articles were reviewed after selecting on various predetermined article criteria. The results shown that there was a contribution of obesity in COVID-19 patients based on the type of treatment, length of treatment, need for intensive care, severity and increased risk of death. It is recommended to maintain a healthy lifestyle while maintaining a normal weight and doing physical activity and exercise every day with a minimum duration of 30 minutes. Thus, it can reduce the accumulation of macrophages in adipose tissue, so if infect COVID-19 do not cause a cytokine storm because chronic inflammation due to obesity.